2011
DOI: 10.5194/acp-11-11335-2011
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei closure study on summer arctic aerosol

Abstract: Abstract. We present an aerosol -cloud condensation nuclei (CCN) closure study on summer high Arctic aerosol based on measurements that were carried out in 2008 during the Arctic Summer Cloud Ocean Study (ASCOS) on board the Swedish ice breaker Oden. The data presented here were collected during a three-week time period in the pack ice (> 85 • N) when the icebreaker Oden was moored to an ice floe and drifted passively during the most biological active period into autumn freeze up conditions. CCN number concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
121
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 57 publications
22
121
4
Order By: Relevance
“…For example, Lathem et al (2013), who measured the CCN activity in the Arctic using aircraft measurements, reported a κ value of 0.32 ± 0.21. Martin et al (2011) inferred a total κ value of 0.33 ± 0.13 during a cruise observation in Longyear- byen, Svalbard. Kammermann et al (2010) reported κ values that varied between 0.07 and 0.21 over an 18-day period within the Arctic Circle in Sweden.…”
Section: Cloud Condensation Nuclei (Ccn) Concentrationsmentioning
confidence: 99%
“…For example, Lathem et al (2013), who measured the CCN activity in the Arctic using aircraft measurements, reported a κ value of 0.32 ± 0.21. Martin et al (2011) inferred a total κ value of 0.33 ± 0.13 during a cruise observation in Longyear- byen, Svalbard. Kammermann et al (2010) reported κ values that varied between 0.07 and 0.21 over an 18-day period within the Arctic Circle in Sweden.…”
Section: Cloud Condensation Nuclei (Ccn) Concentrationsmentioning
confidence: 99%
“…The quality of all ship-board aerosol sampling was monitored using various tracers and thresholds to identify potential contamination from local ship and snowmobile pollution. Further details on the quality and data processing of ship-based aerosol and CCN measurements are available in Heintzenberg and Leck (2012) and Martin et al (2011), respectively. Vertical profiles of aerosol concentrations were made using a helicopter (Kupiszewski et al, 2013).…”
Section: Aerosol Number Concentrationsmentioning
confidence: 99%
“…[25] Most studies that strive for CCN closure utilize bulk chemical analysis to drive predictive calculations based on the known hygroscopicity of various substances [e.g., Broekhuizen et al, 2006;Martin et al, 2011]. Often, the incorporation of external mixing assumptions are required to gain closure due to the importance of the number concentration-weighted mixing state of particles rather than widely used bulk aerosol mass concentration measurement techniques [Wex et al, 2010b].…”
Section: Ccn Activity and Mixing Statementioning
confidence: 99%